Pengaruh Iklim Kerja terhadap Peningkatan Disiplin Kerja Karyawan PT. Rejeki Abadi Sakti - M. Jhon; Meryanto Eko Saputro (Jurnal Pendidikan Manajemen Transportasi, 2024)
This study aims to determine the effect of work climate in order to improve employee work discipline at PT. Rejeki Abadi Sakti. The sample used in this study was 30 people. The research method used is a descriptive analytical survey research method with a qualitative approach, by providing a description of each question variable regarding the responses of respondents or employees who are the research samples. Based on the results of the data description obtained, the work climate is able to improve employee work discipline, which means that the better the work climate, the more work discipline will be improved. The conclusion drawn is that the work climate can improve employee work discipline at PT. Rejeki Abadi Sakti The suggestions that can be given as input are that it should be a reference and used as material to improve employee work discipline; the emergence of employee awareness to continuously improve self-discipline; it is necessary to establish more binding rules regarding work discipline; it is necessary to create a conducive work climate so that employees can work more optimally, such as improving and improving qualified school facilities and infrastructure, improving employee welfare, giving awards to employees who excel and others.